2018
DOI: 10.1155/2018/4658583
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet and Alcohol Intake Promotes Inflammation and Impairs Skin Wound Healing in Wistar Rats

Abstract: The wound-healing process is complex and remains a challenging process under the influence of several factors, including eating habits. As improper diets may lead to disorders such as dyslipidemia, insulin resistance, and chronic inflammation, potentially affecting the tissue ability to heal, we decided to investigate the effect of a high-fat diet and alcohol intake on the inflammatory process and skin wound healing in Wistar rats. Male rats (n = 30) were individually housed in cages with food and water ad lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 64 publications
(79 reference statements)
1
18
0
2
Order By: Relevance
“…These authors showed that Dx reduced lipid peroxidation in the brain, thus protecting the tissue from the action of free radicals. Another important marker of the action of ROS and RNS in the tissue is the high content of carbonylated protein, which indicates protein oxidation [66,81]. In the present study, after treatment with Dx, only using the lower dose, reduced levels of protein carbonylation were observed, suggesting the antioxidant secondary action of this drug.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 54%
See 1 more Smart Citation
“…These authors showed that Dx reduced lipid peroxidation in the brain, thus protecting the tissue from the action of free radicals. Another important marker of the action of ROS and RNS in the tissue is the high content of carbonylated protein, which indicates protein oxidation [66,81]. In the present study, after treatment with Dx, only using the lower dose, reduced levels of protein carbonylation were observed, suggesting the antioxidant secondary action of this drug.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 54%
“…Besides, the formation of new vessels is directly linked to the formation of a new matrix, called granulation tissue, rich in vessels and cells. When the process advances, the number of vessels and cells decreases, but the number of fibers increases, which characterizes mature scar tissue [66]. Therefore, new effective treatments should promote intense neoangiogenesis at the start of the repair pro-cess and reduce the levels of vessels at the end of the process.…”
mentioning
confidence: 99%
“…It has been shown that acute ethanol exposure reduces collagen content and angiogenesis and as a result delays wound closure in mice 36 . More recently, it has been demonstrated that chronic administration of ethanol in combination with high‐fat diet delays skin wound healing by decreasing collagen type I and III contents, increasing the levels of inflammatory cytokines and promoting oxidative stress 37 . Similarly, ethanol alters several liver homeostatic processes including cytoskeleton contractility and collagen type‐1 content, which drive tissue fibrosis and scar formation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CHD has been associated with poor gastric, dermal, and bone wound healing outcomes [12], increasing the risks for morbidity and mortality following surgery or trauma [13]. Several lines of evidence suggest that this defect is primarily mediated by excessive inflammation associated with CHD, impairing the function of innate immune cells and thus compromising the process of tissue repair [14].…”
Section: Introductionmentioning
confidence: 99%